2023
DOI: 10.1007/s00464-022-09857-9
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal function and non-acid reflux evaluated by impedance-24 h-pH-metry, high-resolution manometry, and gastroscopy after one-anastomosis gastric bypass—outcomes of a prospective mid-term study

Abstract: Background One-Anastomosis Gastric Bypass (OAGB) is the third most common bariatric operation for patients with obesity worldwide. One concern about OAGB is the presence of acid and non-acid reflux in a mid- and long-term follow-up. The aim of this study was to objectively evaluate reflux and esophagus motility by comparing preoperative and postoperative mid-term outcomes. Setting Cross-sectional study; University-hospital based. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Some authors have urged performing diversion of the biliary flow away from the gastro–jejunal anastomosis whether by conversion to RYGB or by adding a Braun anastomosis to the omental patch [ 23 ]. In fact, Felsenreich and colleagues showed overt bile reflux in endoscopy five years following OAGB in a significant minority of patients (43%) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have urged performing diversion of the biliary flow away from the gastro–jejunal anastomosis whether by conversion to RYGB or by adding a Braun anastomosis to the omental patch [ 23 ]. In fact, Felsenreich and colleagues showed overt bile reflux in endoscopy five years following OAGB in a significant minority of patients (43%) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is likely that re ux after OAGB encompasses a combination of acid re ux, bile re ux, or a mixture of both (Nehmeh et al, 2021). Furthermore, studies conducted by Musella et al , and Felsenreich et al (Felsenreich et al, 2023) have demonstrated three types of re ux, with non-acid re ux being more prevalent. Additionally, Doulami et al (Doulami et al, 2018) compared acid and non-acid re ux before and after OAGB, revealing a decrease in acid re ux episodes but an increase in non-acid re ux episodes following the procedure.…”
Section: Eldredge Et Al Showed That Br Into the Esophagus Can Be Carc...mentioning
confidence: 96%